Increased Vascular Permeability in the Bone Marrow Microenvironment Contributes to Disease Progression and Drug Response in Acute Myeloid Leukemia - Passaro, Diana (Cancer Cell, 2017)
The biological and clinical behaviors of hematological malignancies can be influenced by the active crosstalk with an altered bone marrow (BM) microenvironment. In the present study, we provide a detailed picture of the BM vasculature in acute myeloid leukemia using intravital two-photon microscopy. We found several abnormalities in the vascular architecture and function in patient-derived xenografts (PDX), such as vascular leakiness and increased hypoxia. Transcriptomic analysis in endothelial cells identified nitric oxide (NO) as major mediator of this phenotype in PDX and in patient-derived biopsies. Moreover, induction chemotherapy failing to restore normal vasculature was associated with a poor prognosis. Inhibition of NO production reduced vascular permeability, preserved normal hematopoietic stem cell function, and improved treatment response in PDX.